Shared Book Reading Promotes Not Only Language Development, But Also Grapheme Awareness in German Kindergarten Children - Wesseling, Patricia B. C.; Christmann, Corinna A.; Lachmann, Thomas (Frontiers in Psychology, 2017)
Effects of shared book reading on expressive vocabulary and grapheme awareness without letter instruction in German kindergarteners (longitudinal; N = 69, 3;0 - 4;8 years) were investigated. Expressive vocabulary was measured by using a standardized test; grapheme awareness was measured by asking children to identify one grapheme per trial presented amongst non-letter distractors. Two methods of shared book reading were investigated, literacy enrichment (additional books) and teacher training in shared book reading strategies, both without explicit letter instruction. Whereas positive effects of shared book reading on expressive vocabulary were evident in numerous previous studies, the impact of shared book reading on grapheme awareness has not yet been investigated. Both methods resulted in positive effects on children’s expressive vocabulary and grapheme awareness over a period of six months. Thus, early shared book reading may not only be considered to be a tool for promoting the development of expressive vocabulary, but also for implicit acquisition of grapheme awareness. The latter is considered an important precondition required for the explicit learning of grapheme-phoneme-conversion rules (letter knowledge).